Metabolic syndrome and risk of ovarian cancer: a systematic review and meta-analysis - Chen, Ziyu; Liu, Zesi; Yang, Hongxia; Liu, Chaosheng; Kong, Fandou (Frontiers in Endocrinology, 2023)
Background MetS is associated with greater morbidity and mortality in relation to a number of malignancies, but its association with ovarian cancer remains contested. The present study was a systematic review and meta-analysis of case-control and cohort studies examining the association between MetS and ovarian cancer risk. Methods The study was registered on the PROSPERO platform in January 2023 (CRD42023391830). Up until February 13, 2023, a complete search was undertaken in PubMed, EMBASE, Web of Science, the Cochrane Library, and ClinicalTrials. On the basis of inclusion and exclusion criteria, eligible studies for meta-analysis were screened to determine the association between MetS and ovarian cancer risk. Results Five studies were included in total, including three cohort studies and two case-control studies. Meta-analysis showed no significant correlation between metabolic syndrome and ovarian cancer (OR=1.29, 95% CI: 0.90-1.84). Significant heterogeneity (I2 = 92.6, P<0.05) existed between the included studies. We performed a subgroup analysis of the risk of bias and showed that only unadjusted stratification of risk of bias for smoking (OR= 3.19, 95% CI: 2.14-4.76) and hysterectomy (OR= 3.19, 95% CI: 2.14-4.76) demonstrated a relationship between metabolic syndrome and ovarian cancer risk. The meta-regression analysis revealed that smoking and hysterectomy excision were substantially linked with heterogeneity (p < 0.05). Conclusion Our research revealed no statistically significant association between MetS and ovarian cancer risk. The prevalence of metabolic syndrome has highlighted the need of enhancing and controlling women’s metabolic health. However, the evaluation of metabolic syndrome as a cancer risk factor may be deceptive and etiologically uninformative.